8 - Genre et vie politique en RDC. L’émergence du leadership féminin aux prises avec les logiques de « domination masculine »: Dieu-merci Aksanti Cirhibuka - Dieu-merci Aksanti Cirhibuka (African Sociological Review, 2021)
This paper analyzes the place and role of women in political and social life in the Democratic Republic of the Congo. The reflections are based on the postulate according to which the participation of men and women in public life is a necessary condition for both economic growth and social progress. Thus, by extending the debate on the perspectives inherent in the need for effective consideration of women’s assets in decision-making spheres, this article leads to two diametrically opposed trends. The first trend sees female leadership as a threat to the dominant male order. This trend allows representative oppositions to emerge between two irreconcilable roles: social incoherence and the risk for social organization. On the other hand, the second trend maintains that a more balanced representativeness between women and men is essential for better governance of society.